Analysis of the Overall Equipment Effectiveness (OEE) to Minimize Six Big Losses of Pulp machine: A Case Study in Pulp and Paper Industries. Issue 1 (June 2019) - Sayuti, M; Juliananda,; Syarifuddin,; Fatimah,
Abstract: Overall Equipment Effectiveness (OEE) is a method of measuring the effectiveness of the use of equipment. This method is known as an application of a Total Productive Maintenance (TPM) program. The ability to clearly identify the source of problem and it causal factors is the main advantage of this method since the improvement effort becomes focused. Pulp and Paper Industries is one of the manufacturing companies that produce dissolving pulp products (rayon fibre). Based on data from the fibre line department, for the period of January - July 2016, the production process of rayon fibre often experienced constraints due to the high downtime and losses in the pulp machine. This resulted in the use of production process equipment that had not been optimal. It is important to find out the source of the problem and its causal factors before the company makes any improvement effort. This study aims to identify equipment losses and measure the achievement of OEE values in the pulp machine. The measurement result shows that the average of the effectiveness of pulp machine for the period of January - July 2016 was 74.01% and based on Japan Institute Of Plant Maintenance (JIPM) the value has not reached the standard that is > 85%, however, there is still possibility for improvement. The losses that give the most significant effect on the overall equipment effectiveness of the pulp machine is reduce speed that was equal to 27.6%. One way to minimize the losses is by maintaining the actual speed of operation and maintaining wear on each pulp machine roll.